A.r.c.h.i.e. as The man from R.I.V.E.R.D.A.L.E. - Doyle, Frank 1917-1996 (Archie Comic Publications, 2019)
A series of stories in which Archie Andrews and his friends are spies working as part of the world defense organization Protect our Planet, or P.O.P.
"All stories previously published and copyrighted by Archie Comic Publications, Inc. (or its predecessors) in magazine form 1966-1967.
"This book contains some material that was originally created in a less socially sensitive time in our society and reflects attitudes that may be interpreted as being unacceptable today. The stories are reprinted here without alteration for historical reference.
Keywords: Spion; Verteidigung; Jugend; Comic